Keberkesanan Pengurusan Sekolah Agama Rakyat Daerah Kuala Muda, Yan, Kedah - Faridah, Hj. Yahya (1998)
The purpose of this study is to identify the level of effectiveness in the management of Sekolah Agama Rakyat (SAR) in term of curriculum management, staff management, communication management and recreational management. This study was done by issuing questionnaires to 165 teachers in SAR in Kuala Muda district. All data obtained was analyzed by using SPSS for window 7.5 software through which percentage, mean and hypothetical test were achieved. The study showed that the level of using effective management in SAR were moderate. There was a significant differences between mean staff management, communication management and recreational management at two types of SAR. There was a significant negative relationship between staff management, communication management, recreational management and score in academic and the most important factor for predicting effective SAR was staff management. Based on this result, SAR administrators are recommended to improve their management knowledge and skill in school management. All SAR are also have to cooperate and perform a board (Yayasan) which will plan, organize and control the quality of SAR.